FAKTOR-FAKTOR YANG MEMENGARUHI NIAT DAN PERILAKU GENERASI Z MENGGUNAKAN APLIKASI INVESTASI REKSA DANA BERBASIS MOBILE - Lintang Selviana Aswan; Wita Juwita Ermawati; Lukytawati Anggraeni (Jurnal Ilmu Manajemen, 2026)
This study examines the factors influencing Generation Z’s intention and use behavior toward mobile-based mutual fund investment applications, integrating UTAUT2 constructs, financial literacy, and habit. A quantitative approach was employed through a purposive survey of 203 app users in Jakarta. Data were analyzed using Partial Least Squares–Structural Equation Modelling (PLS-SEM) via SmartPLS 4 to assess relationships among variables. The results indicate that performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and financial literacy positively affect behavioral intention. Habit does not significantly influence behavioral intention but has a direct effect on use behavior, highlighting the role of automaticity and behavioral inertia, where habitual behavior drives actions without conscious intention. Behavioral intention remains the main predictor of use behavior, while other factors such as facilitating conditions, financial literacy, hedonic motivation, price value, and habit also exert direct effects on usage. The findings provide several practical implications for platform managers and regulators, including the development of digital financial literacy programs, the enhancement of system convenience, and collaborative educational campaigns with regulatory bodies such as OJK or BEI. In addition, the study contributes to the literature on UTAUT2 and digital investment behavior among Generation Z in the Southeast Asian context, particularly in understanding the roles of habit and financial literacy. This study is limited to mobile mutual fund app users in Jakarta, so generalization to the broader Generation Z population or other investment instruments should be done with caution.